The body, food and eating - Maj, Agnieszka; Wójtewicz, Anna (Body and society. Sociology of the body in research and theoretical concepts, 2023)
In this chapter, I offer an insight into the issue of human sexuality within the context of the body and embodiment, drawing on classical literature in the area and more recent field studies. I aim to highlight diverse analytical avenues of problematizing and analyzing how people make sense of, experience, and navigate within the sexual sphere of their lives. I also elucidate how the issues at hand are embraced from the sociological point of view, especially concerning the sociology of the body. In the first section, I draw on ‘classical’ sociological works undertaking the issue of sexuality to offer a theoretical framework for the sociological conceptualization of human sexuality as the research subject. Also, I offer insights into queer theory and symbolic interactionist approaches to human sexuality. In the next section, I present concepts and phenomena most commonly encountered in the literature concerning human sexuality. In the subsequent section, I discuss research studies undertaking specific areas of human lived experience within sexuality. I aim to highlight approaches to conceptualizing diverse substantial areas of human sexuality and (embodied) experiences therein. For that, instead of focusing on specific research subjects, I elucidate analytical frameworks and concepts that guided the argument. To meet that end, I discuss how internalized social norms and values have an impact on human endeavors; how meaning-making is a context-dependent process; how ‘deviance’ is socially constructed; how gendered dominance leads to conflictive interactions and makes violence against the superordinate incomprehensible; and how the way of communicating has an impact on sexual socialization.